ANALISA PENGARUH MODAL KERJA, POTONGAN HARGA, DAN PENJUALAN TERHADAP LABA BERSIH PERUSAHAAN MANUFAKTUR MAKANAN DAN MINUMAN TERDAFTAR DI BURSA EFEK INDONESIA - Soewignyo, Tonny (JBE (Journal of Business and Economics); Volume 13 No.1, 2014 JBE UNKLAB, 2014)
The purpose of this research was to see whether there was an effect of working capital, price reduction, and sales variables to net income if they were simultaneously tested.  The research sample taken focuses on thirteen manufacture companies especially on the food and beverage sector listed in Indonesia Stock Exchange in 2012.  This research design used is causal method with multiple and simple regression analysis.  The result of the study found that there was significant effect of working capital, price reduction, and sales variables to net income. O ut of the three variables, sales and working capital variable s that have a significant effect on the n et income . The implication for food and beverage  manufacturing companies is the need to as much as possible avoid discount offerings.